â€œAsyhurul Hurumâ€ Tirakat Education in Exact Science Perspectives, Social, Psychology. - Hartono, Djoko; Jannah, Roudlotul; Azizah, Nilatul (Journal Intellectual Sufism Research (JISR), 2020)
Abstract. Everyone, especially students from the Jagad 'Alimussirry Surabaya Islamic Boarding School, is indispensable for everyone, especially the students of the' Alimussirry 'Jagad Islamic Boarding School. Tirakat is studied from the perspective of exact science, social, and psychology. Tirakat is applied to train students to improve emotional intelligence, improve the brain's working system, and increase the sense of empathy for others. This research uses a cognitive paradigm with a qualitative approach. Literature review and interview methods were used to obtain research data. Interviews were conducted with 15 students. The results of this study state that inexact science, Tirakat Asyhurul Hurum can increase concentration in learning, increase metabolism, and increase immunity. Socially, Tirakat Asyhurul Hurum can increase feelings of empathy for others and Tirakat Asyhurul Hurum. psychologically able to increase emotional intelligence in a person.